Repopulating microglia promote brain repair in an IL-6-dependent manner - Willis, EF; MacDonald, KPA; Nguyen, QH; Garrido, AL; Gillespie, ER; Harley, SBR; Bartlett, PF; Schroder, WA; Yates, AG; Anthony, DC; Rose-John, S; Ruitenberg, MJ; et al. (Cell Press, 2020)
Cognitive dysfunction and reactive microglia are hallmarks of traumatic brain injury (TBI), yet whether these cells contribute to cognitive deficits and secondary inflammatory pathology remains poorly understood. Here, we show that removal of microglia from the mouse brain has little effect on the outcome of TBI, but inducing the turnover of these cells through either pharmacologic or genetic approaches can yield a neuroprotective microglial phenotype that profoundly aids recovery. The beneficial effects of these repopulating microglia are critically dependent on interleukin-6 (IL-6) trans-signaling via the soluble IL-6 receptor (IL-6R) and robustly support adult neurogenesis, specifically by augmenting the survival of newborn neurons that directly support cognitive function. We conclude that microglia in the mammalian brain can be manipulated to adopt a neuroprotective and pro-regenerative phenotype that can aid repair and alleviate the cognitive deficits arising from brain injury.